Index-based dietary patterns and stomach cancer in a Chinese population. Issue 6 (November 2021) - Zhu, Yuhui; Jeong, Somee; Wu, Ming; Zhou, Jin-Yi; Jin, Zi-Yi; Han, Ren-Qiang; Yang, Jie; Zhang, Xiao-Feng; Wang, Xu-Shan; Liu, Ai-Ming; Gu, Xiao-ping; Su, Ming; et al.
Abstract : Objectives: Dietary factors are of importance in the development of stomach cancer. This study aims to examine index-based dietary patterns associated with stomach cancer in a Chinese population. Methods: Using data from a population-based case-control study conducted in Jiangsu Province, China, we included a total of 8432 participants (1900 stomach cancer cases and 6532 controls). Dietary data collected by food frequency questionnaire was evaluated by modified Chinese Healthy Eating Index-2016 (mCHEI-2016) and the US Healthy Eating Index-2015 (HEI-2015). Multiple logistic regression analyses were applied to examine the association of mCHEI-2016 and HEI-2015 with stomach cancer while adjusting for potential confounders. The possible interactions between mCHEI-2016 or HEI-2015 and established risk factors were explored. Results: Among nonproxy interviews, after adjusting for potential confounding factors, a higher score of sodium, reflecting lower intake per day, was inversely associated with stomach cancer [odds ratio (OR), 0.95; 95% CI, 0.91–0.99 for mCHEI-2016; OR, 0.97; 95% CI, 0.94–0.99 for HEI-2015]. No clear associations with stomach cancer were identified for total scores of HEI-2015 (OR, 0.98; 95% CI, 0.87–1.10 with a 10-point increase, P trend = 0.98) and mCHEI-2016 (OR, 1.05; 95% CI, 0.94–1.17 with a 10-point increase, P trend = 0.22). However, the relation between stomach cancer and the mCHEI-2016 was modified by BMI, with a possible inverse association in normal-weight subjects. Conclusions: Our findings highlight that reduced intake of dietary sodium would prevent the development of stomach cancer. The data indicate a heterogeneity between normal weight and overweight's dietary factors in relation to stomach cancer. Abstract : Supplemental Digital Content is available in the text.